Levels of forgiveness and its relationship with Symptoms of Depression in a sample of students of Faculty of Education in Damascus University (Damascus University Journal of educational and Psychologyical sciences, 2021)
The research aimed at identifying the level of forgiveness, and the level of symptoms of depression ,and identifying the predictability of depression symptoms through forgiveness , gender , the year of study , in addition to identifying the relationship between forgiveness and symptoms of depression, and exploring the differences among students in forgiveness  according to the gender ,as well as exploring the differences among students in forgiveness and symptoms of depression according to the year of study. The sample of this research consisted of (110) students: (17) males, (93) females.The instruments of the research included forgiveness scale and depression scale. Results showed the following: There was a high level of forgiveness and a low level of depression symptoms among the sample of the research. In addition, forgiveness predicts symptoms of depression symptoms. Moreover, forgiveness of self and forgiveness of situations predicts symptoms of depression. There was a negative statistically significant correlation between forgiveness and symptoms of depression. There were no statistically significant differences in forgiveness according to the gender. There were statistically significant differences in forgiveness according to the year of study, and these differences were in favor of the fifth year of study . Also, there were statistically significant differences in symptoms of depression according to the year of study, and these differences were in favor of the first year of study.
Keywords: forgiveness; Depression